AGAMA DAN TANTANGAN BUDAYA MODERN PERSPEKTIF ISLAM - Arief Rifkiawan Hamzah Heri Cahyono (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
This article was written to explain the relation between religion and modern culture in the perspective of Islam and explaining the attitudes of religious in their response to modern culture. Modern culture provides a great challenge for Muslims in the world, especially in Indonesia. It certainly affects the existence of the world's religions, especially Islam. Modern culture is considered to make a significant change and threaten the existence of religion within religious communities. Religious needs of mankind is shrinking as the development of modern culture, even religion in modern culture can no longer be needed, because all human needs can be fulfilled with the advancement of science and technology. On the other hand, religion is used as guidance in the face of circumstances, it looks less so in response to the progress of time. For the relationship between religion and modern culture needs to be established format, which is described in this article that the relation between the two begins with vertical and horizontal relationships, which is then translated into relations in the form of indigenization, negotiation, and conflict. From this relation, there arose attitudes beragamam people, that refuse to accept fully and analyzed first before deciding.